RISK FACTOR OF GREEN TOBACCO SICKNESS (GTS) AT THE CHILDREN ON TOBACCO PLANTATION - Dewi Rokhmah; Khoiron Khoiron (UPT Penerbitan Universitas Jember, 2016)
Tobacco farmers are at risk of developing occupational diseases associated with exposure to pesticides and absoption of wet tobacco leaves nicotine through the skin that is called Green Tobacco Sickness (GTS). In 2013 the result of the research showed that 66% of tobacco farmers had GTS symptom. And the continuing research at 2014 showed that 79,2% of tobacco farmer had cotinine degree on the blood was 13,64 mg/ml (more than normal standard) means at GTS symptom. Besides that, the result of observation by researcher showed that there were a lot of children was involved in tobacco plantation in Jember Regency. This research aimed to anayze the risk factor of GTS symptom at children on tobacco plantation, consist of : individual characteristic factors (age, gender, education, connection with the owner of tobacco plantation, period being tobacco farmer) and behaviour factors (knowledge, attitudes, and actions towards GTS), and environmental factors (Humidity, rainy, geographic condition, and irrigation). This study used an analytical approach with survey method and using cross-sectional design, to analyze the dinamic corelation between risk factors with the effects, with observation approach or collecting the data in point time approach. This study was conducted at 120 tobacco farmer from 2 districts in Jember regency which is a center of tobacco production in September to December 2014. Data was Collected by interview with quitionare and observation to the children that working in tobacco plantation. Data were analyzed by descriptive statistic. The results showed that there was 2,5% of children than involved in tobacco plantation. Most of them were male. They aged was 15-18 years old, graduated from elentary, junior and senior high school. The salary was less than one million in a month, and working in fobacco plantation more than 10 years and having smoking habit. They used save protection tools (glooves, long dress, eye protection) rarely. A few of them did not higiene personal after working in tobacco plantation. Although they ever got GTS symptom (nausea, dizzy, faint, difficul to breath, sleeping disturbance). It is needed a socialization in groups of tobacco farmers about the prohibition to involve children in tobacco plantation and the the prevention of GTS symptoms in children through behavioral approach by means of a shower and change clothes after working in the tobacco plantation, and the use of waterproof clothing, gloves and boots.